2013
DOI: 10.1111/pce.12245
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and anatomical determinants of mesophyll conductance in wild relatives of tomato (Solanum sect. Lycopersicon, sect. Lycopersicoides; Solanaceae)

Abstract: Natural selection on photosynthetic performance is a primary factor determining leaf phenotypes. The complex CO2 diffusion path from substomatal cavities to the chloroplasts -the mesophyll conductance (gm) -limits photosynthetic rate in many species and hence shapes variation in leaf morphology and anatomy. Among sclerophyllous and succulent taxa, structural investment in leaves, measured as the leaf dry mass per area (LMA), has been implicated in decreased gm. However, in herbaceous taxa with high gm, it is l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
87
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(94 citation statements)
references
References 77 publications
5
87
0
2
Order By: Relevance
“…This fits to some extent with recent observations (Tholen & Zhu ; Muir et al . ) even if it is clear that tissue density is by far not the only determinant of g m .…”
Section: Discussionmentioning
confidence: 98%
“…This fits to some extent with recent observations (Tholen & Zhu ; Muir et al . ) even if it is clear that tissue density is by far not the only determinant of g m .…”
Section: Discussionmentioning
confidence: 98%
“…4) revealed that the decrease of mesophyll conductance is the most important factor limiting A in mutants. Mesophyll structural features, including T cell-wall , S m , and S c are believed to play a central role in determining g m 22, 24, 26, 31 . Using the 1-D anatomical model, we analyzed the impacts of leaf anatomical traits on mesophyll conductance by considering all major leaf anatomical traits as described by Tosens et al .…”
Section: Discussionmentioning
confidence: 99%
“…Rapid changes in g m have been documented (Flexas et al 2008;Warren 2008); however, these g m changes vary with leaf structural parameters such as cell packing, shape and wall thickness Tomás et al 2013). The relationship between CO 2 diffusion processes and morphoanatomical traits has been well documented, and many related trade-offs have been described (Ocheltree et al 2012;Giuliani et al 2013;Tanaka et al 2013;Muir et al 2014). However, most of these results were obtained across species, cultivars or genetic stocks.…”
Section: Introductionmentioning
confidence: 90%